Violence among community elderly and its relationship with the nutritional status and sociodemographic characteristics - Wesley Ferreira de Moraes Brandão; Matheus Araruna de Souza; Gleicy Karine Nascimento de Araújo; Renata Clemente dos Santos; Luana Rodrigues de Almeida; Rafaella Queiroga Souto (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To verify the prevalence of violence among elderly community members and its relationship with nutritional status and sociodemographic characteristics. Method: Cross-sectional and analytical study developed with 159 community elderly registered at a Family Health Unit in Recife/Pernambuco between March 2016 and March 2017. The Brazil Old Age Schedule, Conflict Tactics Scales and Mini Nutritional Assessment were used as data collection instruments. Data received descriptive and inferential statistical treatment. Results: Among the elderly classified as with violence, there was a predominance of psychological violence (64.3%), and the majority were at risk for malnutrition (54.3%). There was an association between 'having a partner' and psychological (48.1%; p=0.02) and physical (48.1%; p=0.03) violence. Logistic regression demonstrated that being in a relationship or being malnourished increases the likelihood of suffering psychological violence (OR=2.63; OR=3.67), just as not being working increases the likelihood of physical violence (OR=5.61). Conclusion: Violence was negatively related to the nutritional status of elderly community members.